PENGARUH MOTIVASI KERJA, KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN DI SAMPOERNA UNIVERSITY - Prila, Lucky; Elmi, Farida (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
Basically, every employee job satisfaction is different, even if they're on the same type of work; it depends on the needs and systems that act on him. This study aims to examine and analyze the effect of work motivation, leadership and organizational culture on job satisfaction. This study uses a quantitative research with correlational format. The analytical method used in this research is multiple linear regressions. The study population employees of Sampoerna University. The sampling method used is Non-Probability Sampling using census. Samples were 66 samples or respondent. Based on the research results that motivation significantly influences employee job satisfaction, leadership significantly influences employee job satisfaction and organizational cultures have a significant effect on employee job satisfaction. Suggested expanding training opportunities for employees, a clear career path in this regard prioritize the employees in filling positions higher to employees who are qualified for the position increment. More frequent interaction required from the leadership to employees who are below to explore the aspirations of his subordinates and show concern for their taste. The importance of disseminating the culture of the company to all members of the organization in the form of posters were on display at the strategic points, meetings as well as direct examples from top management on corporate culture